DETERMINING THE POPULARITY OF ISLAND TOURIST DESTINATIONS USING GOOGLE TRENDS ANALYSIS - I Gusti Bagus Rai Utama; I Wayan Ruspendi Junaedi; PA Andiena Nindya Putri; Ni Putu Dyah Krismawintari (International Journal of Social Science, 2022)
This study uses the Google Trends Tool to determine the popularity of four island tourist destinations in the world, namely Phuket, Bali, Hawaii, and Langkawi. The most popular tourist destinations are Hawaii, then Bali, then Phuket, and finally Langkawi. The results of the analysis show that from the beginning of 2000 to the end of 2021, almost all island tourist destinations in the world. Phuket destination is very popular for tourists who come from Thailand itself, Russia, Turkey, Hong Kong, and Singapore. Bali is very popular among tourists from Indonesia, the Netherlands, India, Australia, and Belgium. Hawaii is very popular among tourists from the United States itself, Japan, Canada, Brazil, and South Korea. While Langkawi is very popular among tourists who come from Malaysia itself, Singapore, Pakistan, Hong Kong, and Egypt.